Serosurvey of Leptospira spp. and Toxoplasma gondii in rats captured from two zoos in Southern Brazil - Pellizzaro, Maysa [UNESP]; Conrado, Francisco de Oliveira; Martins, Camila Marinelli; Joaquim, Samea Fernandes [UNESP]; Ferreira, Fernando; Langoni, Helio [UNESP]; Biondo, Alexander Welker (Soc Brasileira Medicina Tropical, 2017)
Introduction: Norway rats (Rattus norvegicus) are zoonotic reservoirs for Leptospira spp. and Toxoplasma gondii, and influence diseases in urban areas. Methods: Free-ranging and laboratory-raised rats from two zoos in southern Brazil were tested for Leptospira spp. and T. gondii using microscopic agglutination and modified agglutination tests, respectively. Results: Overall, 25.6% and 4.6% free-ranging rats tested positive for Leptospira spp. and T. gondii, respectively, with co-seropositivity occurring in two animals. For laboratory-raised rats, 20% tested positive for Leptospira spp. Also, Leptospira biflexa serovar Patoc and Leptospira noguchii serovar Panama were found. Conclusions: Serosurveys can show the environmental prevalence of zoonotic pathogens.
Keywords: Norway rat; Leptospirosis; Toxoplasmosis